Classification of heart sounds using wavelets and neural networks - Hadi, H. M.; Mohd Yusoff, Mashor; Mohamed, M. S.; Tat, K. B. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org